Regulatory Gaps in Data Protection and Proportionality in Digital Banking: Legal Issues in ASEAN - Agustianto Agustianto; Michael T. Sacramed; Winda Fitri; Nadia Carolina Weley; Hari Sutra Disemadi (Syura: Journal of Law, 2026)
This study examines the legal gaps in regulating data proportionality in ASEAN digital banking, particularly in Indonesia, the Philippines, and Malaysia. The main legal issue lies in the absence of clear standards governing the limitation, justification, and classification of personal data, which leads to excessive and potentially invasive data processing practices in digital banking systems. This research aims to examine the concept of data proportionality in digital banking and to assess the adequacy of legal frameworks governing data proportionality in Indonesia, the Philippines, and Malaysia in order to identify existing regulatory gaps. This study employs a normative legal research method with a comparative approach. The findings reveal that although all three countries have established data protection frameworks, none comprehensively integrate data proportionality into digital banking regulations, resulting in fragmented and ineffective legal protection. Indonesia lacks detailed standards and risk-based mechanisms, while the Philippines and Malaysia show regulatory gaps in governing conventional digital banking services. These weaknesses contribute to increased risks of privacy violations and legal uncertainty. Therefore, this study suggests the need for regulatory reform, including clearer data classification, proportionality standards, and mandatory risk assessments, to ensure a balance between digital banking innovation and the protection of consumer privacy rights.